Fourier transform spectrum of 34SO2 in the region of the v2 bending fundamental band; High Resolution Molecular Spectroscopy, HRMS 2018 - Zyatkova (Ziatkova) A. G. Anastasiya Georgievna; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Bauerekker Z. Zigurd; Sydow Ch. Christian; Mellau G. Georg Ch; Quack M. Martin; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich (2018, 2018)
Title screen